Application of modern technologies to international development - Agency for International Development, Office of Science and Technology; United States (Washington, D.C. : National Technical Information Service (NTIS), 1974)
The primary objective is to bring certain U.S. technical publications to the attention of interested individuals and organizations in developing countries to foster the transfer of technologies to these countries. The reports described herein represent the results of research funded by the United States Government. Beginning with this issue, the subject coverage is expanded with emphasis on areas of particular interest in developing countries.
Includes bibliographical references and index.
ne 10/04/2018
Loans
Keywords: Technological innovation